“Guía didáctica de la danza andina de la provincia de Tungurahua, dirigida a estudiantes de 3 a 5 años del “Centro Integral de Recreación, Aprendizaje y Conocimiento” año 2023.” - Toasa Chicaiza, Ingrith Dayana (2024)
The objective of this research work is to initiate a new didactic learning methodology by facilitating teachers in the area of art, dance, and culture at the Comprehensive Center for Recreation, Learning, and Knowledge to help promote dance more quickly and simply at the same time helping teachers to understand better the area of dance along with its definitions, basic steps, how to apply them and choreographies that they can perform. It was applied to children from preschool to primary education. In their short apprenticeship, they will be able to learn in a fun way the different types of dances that our province of Tungurahua offers us, thanks to the variety of ethnic cultures that exist. Together with the children from 3 to 5 years old, activities such as playful games to warm up were carried out, and dances that exist along with their main step to achieve coordination were seen and thus integrated several steps in order to create a choreography that manages to attract the child's attention and teach culture and its tradition. Favorable results were obtained since the children contributed to this work, paying interest and attention to each class given. So, this teaching guide offered is an excellent learning tool.